Hemodynamic effect of transcatheter patent ductus arteriosus closure on gradient across stenotic aortic valve in a patient with co-existing bicuspid aortic valve, severe aortic stenosis and patent ductus arteriosus: a rare case report - Upadhyay, Amar Nath; Khati, Asmita; Tripathi, Richa; Saijeet (International Journal of Research in Medical Sciences, 2025)
Bicuspid aortic valve is the commonest congenital heart disease. It progresses to aortic stenosis, aortic regurgitation and aortopathy. However, most of the patients remains asymptomatic. Patent ductus arteriosus is relatively common congenital heart disease presenting as left to right shunt and pulmonary over circulation. Co-existence of bicuspid aortic valve, severe aortic stenosis and Patent ductus arteriosus is rare. These diseases are amenable to transcatheter treatment. Transcatheter closure is recommended treatment for patent ductus arteriosus and balloon aortic valvotomy is used as temporizing measure in paediatric severe aortic stenosis to relieve left ventricular outflow tract obstruction. Hemodynamic effect of one disease can affect the severity of other co-existing disease. In this case report we tried to understand hemodynamic effect of transcatheter closure of patent ductus arteriosus on severity of aortic stenosis. We found that transcatheter closure of patent ductus arteriosus decreased the peak-to-peak gradient across aortic valve.